2015
DOI: 10.1002/jcla.21873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantitative Real‐Time PCR as a Hepatitis C Virus Supplementary Test After RIBA Discontinuation

Abstract: Laboratory testing plays a major role in hepatitis C virus (HCV) diagnosis and patient follow-up. The high false positive rates of HCV screening tests require confirmation through a supplementary test. According to the 2003 CDC guidelines, recombinant immunoblot assay (RIBA) is indispensible to confirm positive screening results and differentiate biologic false positivity from true HCV exposure. However, RIBA has been permanently discontinued since 2011. In the 2013 update of its guidelines, CDC called for fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…One patient showed a marked decline in the S/CO ratio to <2 within only two years. A high S/CO ratio with a negative NAAT may be regarded as a resolved infection [ 30 ]. However, in the patients with spontaneous recovery after infection without subjective symptoms (15–45%) [ 4 ], it is difficult to distinguish false-positive results from low S/CO ratio solely on the basis of their medical history, as they overlap with the false-positive results at low S/CO ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient showed a marked decline in the S/CO ratio to <2 within only two years. A high S/CO ratio with a negative NAAT may be regarded as a resolved infection [ 30 ]. However, in the patients with spontaneous recovery after infection without subjective symptoms (15–45%) [ 4 ], it is difficult to distinguish false-positive results from low S/CO ratio solely on the basis of their medical history, as they overlap with the false-positive results at low S/CO ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Some biochemical tests (e.g., alanine aminotransferase, albumin, cholesterol) are helpful in diagnosing HCV infection but are only distinctive in acute HCV infection (data not shown). In some studies, however, there was no difficulty in diagnosing HCV infection despite the permanent discontinuation of RIBA [ 30 ]. Our study demonstrated that positive results would not seem to be conclusive of HCV infection without supplemental RIBA testing.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it is stated that RIBA is needed for patients with EIA reactive, NAAT negative results, thus a better evaluation could be made by following these patients who recovered from HCV infection. Nevertheless, it has been stated that neglecting RIBA has a minimal effect on HCV diagnosis, provided that the anti-HCV S / Co ratio is included in the diagnostic algorithm [37]. Despite the decision of CDC to remove RIBA from the diagnostic algorithm for HCV, some authors reported that their results indicate the RIBA should continue to be used [10].…”
Section: The European Research Journal 2022mentioning
confidence: 99%